Development of Problem Based Learning LKPD on Akiah Akhlak Lessons in Class VIII at Mts Al-Ma'arif Brudu Jombang - Khusnul Khotimah; Candra Hermawan; M Farid Nasrulloh (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This research is a development research that aims to develop Student Worksheets (LKPD) based on Problem Based Learning on Akidah Akhlak subjects at MTs AL-Ma'arif Brudu. One of the functions of ADDIE is to be a guide in building training program tools and infrastructure that is effective, dynamic and supports the performance of the training itself. Data Analysis Techniques here are divided into 2, the first process is: Qualitative data which is data about the process of making PBL-based LKPD, such as suggestions and input for improving this LKPD product. The second process: Quantitative Data Analysis in the form of expert validation, learning test results and student response questionnaires about the assessment of the product developed. Analyzed using descriptive statistics. The results of the study of learning using student worksheets, the first conclusion is from the results of the assessment of the experts obtained a score for media experts 86.6% with a very decent category and 79.66% material experts with a decent category. The results of the second study were from student learning test scores, namely the pretest and posttest scores. With the average in the aspect of student acceptance of student worksheets is 82.5%, the average obtained from the LKPD design is 81.37% in the aspect of implementing problem-based learning LKPD learning facilities is 81.37%, the percentage on the Aspect The quality of learning through student worksheets (LKPD) is 80.19%. With the acquisition of the use of learning media in student worksheets is 80.88%, it is declared feasible and can be used in classroom learning. So with the acquisition of the percentage of each aspect will be taken the average of all aspects to make conclusions. The average percentage of all aspects is 82.40%, so this based learning-based LKPD media is suitable for use in learning the madrasa.